SENSITIVITAS VARIASI NILAI CBR SUBGRADE TERHADAP DESAIN PERKERASAN LENTUR PADA JALAN NASIONAL - Fricilia, Maya; Rizky Febriyan, Alief (Civil Engineering, Faculty of Engineering, Universitas Tunas Pembangunan Surakarta, 2025)
National road projects usually use flexible pavement types because they can adapt to diverse soil conditions and are comfortable to use. In the construction project for JLS Lot 1A Brumbun – P. Sine, there is soft soil condition at STA 4+050 with low CBR value, while at STA 5+315, the CBR is high due to excavation of soft rock. However, throughout the planned road, only one thickness design of the pavement is used. The location also has subsoil that often experiences water seepage, causing saturation and potentially leading to consolidation and ground settlement. Therefore, a study was designed to analyze the effect of variations in CBR values on pavement thickness and provide recommendations for pavement thickness that can prevent ground settlement due to saturated soil, considering the thickness of the layers based on field CBR values using MDPJ 2017, Pt T-01-2002-B, and MDPJ 2024. The data collection method used secondary data from the project and conducted a literature study, resulting in the finding that the CBR of the subgrade can affect the thickness of the pavement in terms of the foundation layer thickness. Recommendations for the thickness of the flexible pavement layers using the MDPJ 2024 method are 4 cm for AC-WC, 14.5 cm for AC-BC, 20 cm for Class A LPA, 15 cm for Class B LPA, and a cement stabilization thickness of 20 cm for CBR <10% and a stabilization thickness of 15 cm for CBR >10%